血浆miR-1290表达水平对口腔鳞状细胞癌患者预后预测的价值 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2020)
OBJECTIVE: To investigate the prognostic value of plasma miR-1290 in patients with oral squamous cell carcinoma (OSCC). METHODS: Seventy patients with OSCC admitted to Danzhou People's Hospital from January 2014 to December 2018 were included in this study. Real-time fluorescence quantitative polymerase chain reaction (PCR) was used to detect the expression of miR-1290 in these patients. The optimal cut-off value of plasma miR-1290 expression was determined by the ROC curve method, and patients with OSCC were divided into the high (n=31) and low (n=39) miR-1290-expressing groups. The clinicopathological features of the two groups were compared, and survival curves were drawn using the Kaplan–Meier method. Risk factors affecting the poor prognosis of patients were analyzed using univariate and multivariate COX regression models. RESULTS: The expression level of plasma miR-1290 in the OSCC group was significantly lower than that in the control group (0.65±0.14 vs. 2.06±0.90; t=13.912, P<0.001). The low expression of plasma miR-1290 appeared to be related to the clinical stage, differentiation degree, tumor diameter, and lymph node metastasis of OSCC (P<0.05). Survival analysis showed that the overall survival rate and the progression-free survival rate of the low-miR-1290 group were significantly lower than that of the high-miR-1290 group (P<0.01). Multivariate COX regression analysis showed that clinical stage, lymph node metastasis, and plasma miR-1290<1.14 were independent risk factors for the poor prognosis of patients with OSCC (P<0.05). CONCLUSION: The expression level of plasma miR-1290 in patients with OSCC significantly decreased, and the low expression of miR-1290 is related to the short survival time of OSCC patients. Thus, miR-1290 may be a potential marker predicting the poor prognosis of OSCC.